Materials Discovery of Stable and Nontoxic Halide Perovskite Materials for High‐Efficiency Solar Cells. (8th April 2019) - Jacobs, Ryan; Luo, Guangfu; Morgan, Dane
Abstract: Two critical limitations of organic–inorganic lead halide perovskite materials for solar cells are their poor stability in humid environments and inclusion of toxic lead. In this study, high‐throughput density functional theory (DFT) methods are used to computationally model and screen 1845 halide perovskites in search of new materials without these limitations that are promising for solar cell applications. This study focuses on finding materials that are comprised of nontoxic elements, stable in a humid operating environment, and have an optimal bandgap for one of single junction, tandem Si‐perovskite, or quantum dot–based solar cells. Single junction materials are also screened on predicted single junction photovoltaic (PV) efficiencies exceeding 22.7%, which is the current highest reported PV efficiency for halide perovskites. Generally, these methods qualitatively reproduce the properties of known promising nontoxic halide perovskites that are either experimentally evaluated or predicted from theory. From a set of 1845 materials, 15 materials pass all screening criteria for single junction cell applications, 13 of which are not previously investigated, such as (CH3 NH3 )0.75 Cs0.25 SnI3, ((NH2 )2 CH)Ag0.5 Sb0.5 Br3, CsMn0.875 Fe0.125 I3, ((CH3 )2 NH2 )Ag0.5 Bi0.5 I3, and ((NH2 )2 CH)0.5 Rb0.5 SnI3 . These materials, together with others predicted in this study, may be promising candidate materials for stable, highly efficient, and nontoxic perovskite‐based solar cells. Abstract : High‐throughput density functional theory (DFT) methods are used to screen 1845 halide perovskite materials in search of nontoxic, stable, optimal bandgap materials with high photovoltaic efficiencies for use in single junction, quantum dot, and tandem Si‐perovskite solar cells. A total of 15 promising halide perovskite materials, including (CH3 NH3 )0.75 Cs0.25 SnI3, ((NH2 )2 CH)Ag0.5 Sb0.5 Br3, CsMn0.875 Fe0.125 I3, ((CH3 )2 NH2 )Ag0.5 Bi0.5 I3, and ((NH2 )2 CH)0.5 Rb0.5 SnI3, are found.